2019
DOI: 10.1214/18-aap1437
|View full text |Cite
|
Sign up to set email alerts
|

Supermarket model on graphs

Abstract: We consider a variation of the supermarket model in which the servers can communicate with their neighbors and where the neighborhood relationships are described in terms of a suitable graph. Tasks with unit-exponential service time distributions arrive at each vertex as independent Poisson processes with rate λ, and each task is irrevocably assigned to the shortest queue among the one it first appears and its d − 1 randomly selected neighbors. This model has been extensively studied when the underlying graph … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…Specific results for power of d choices policies when h N =N are presented in Graham [12], see also Luczak and McDiarmid [21]. Budhiraja et al [3] considers also such a local interaction for a queueing network with an underlying graph which is, possibly, random, with jumps of size 1. In this setting when the graph is deterministic, the mean-field analysis can be carried out by using standard arguments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific results for power of d choices policies when h N =N are presented in Graham [12], see also Luczak and McDiarmid [21]. Budhiraja et al [3] considers also such a local interaction for a queueing network with an underlying graph which is, possibly, random, with jumps of size 1. In this setting when the graph is deterministic, the mean-field analysis can be carried out by using standard arguments.…”
Section: Resultsmentioning
confidence: 99%
“…In particular H N (1)=H N , one denotes by h N the cardinality of H N . Relation (3) gives the property that the associated graph is symmetrical that is, if i∈H N (j) then j∈H N (i). We give some simple situations of graphs satisfying these assumptions.…”
Section: The Stochastic Modelmentioning
confidence: 99%
“…Suppose that A(t−) = ∅. By (14) and the fact that G N is connected, we know that either |S(t−)| = 0 or |S(t−)| = N , contradicting (11). Thus, A(t−) = ∅.…”
Section: Proof Of Lemma A1mentioning
confidence: 97%
“…In the context of load balancing, Mukherjee et al [27] studied the join-the-shortest queue (JSQ) policy on general graphs, and showed that this policy is optimal in some sense, as long as the expected degree diverges fast enough as a function of the number of servers. Similarly, Budhiraja et al [10] studied the local power-of-d scheme on graphs, and showed that as long as the minimum degree of the graph diverges, and the degree-weighted adjacency matrix of the graph is asymptotically doubly-stochastic, the occupancy process converges to the same system of ODEs as that on the complete graph.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation